Moving Ahead into the Past: Historical Contexts in Recent Polish Cinema - Anessi, Thomas (Wydawnictwo Naukowe UAM w Poznaniu; Wydawnictwo PWSFTViT w Łodzi, 2012)
The article looks at treatments of Poland’s 20th-century history in Polish films made over the last several years. Since 2007, Polish cinema has seen an explosion of films dealing in various ways with the history of the last century. These include mega-productions by directors known for making historically themed films, like Wajda’s Katyń or Hoffman’s 1920. Battle of Warsaw, and traditional historical dramas dealing with iconic personalities (Rafał Wieczyński’s Popiełuszko. Freedom Is Within Us) and moments in time (Antoni Krauze’s Black Thursday. Janek Wiśniewski Fell). However, a number of other works make use of historical settings from the last century in new and innovative ways. Most choose smaller-scale, less grand approaches to the past, though without abandoning an ambition to accurately depict the times they portray. Films focused on issues related to family and personal relationships, such as Jan Kidawa-Błoński’s Little Rose or Borys Lankosz’s Reverse, likewise speak about life during communism, but attempt to do so without repeating clichéd images by engaging new problems or returning to familiar ones using new techniques. Lastly, memory often plays an important role as a source of knowledge about the past, and as a filter for mediating experiences of it. This can be best seen in Rafael Lewandowski’s The Mole, Władysław Pasikowski’s Consequences (Pokłosie), and Wojciech Smarzowski’s Dark House. Archival evidence, memories of relatives, and the camera itself are used in the films to pose questions about the subjectivity inherent to film as a means of learning about the past.

Artykuł przygląda się sposobom podejmowania tematów z dwudziestowiecznej historii Polski w polskich filmach nakręconych w ciągu ostatnich kilku lat. Od 2007 roku zaobserwować można eksplozję filmów zajmujących się historią minionego wieku. Zaliczają się do nich wielkie produkcje reżyserów znanych z podejmowania problemów historycznych, jak film Andrzeja Wajdy Katyń czy Jerzego Hoffmana 1920. Bitwa warszawska, a także tradycyjne dramaty historyczne opowiadające o ikonicznych bohaterach (Popiełuszko. Wolność jest w nas Rafała Wieczyńskiego) i wydarzeniach (Czarny Czwartek. Janek Wiśniewski padł Antoniego Krauze). Jednakże odnaleźć też można cały szereg filmów, które przetwarzają tematy historyczne ostatniego wieku na nowe i innowacyjne sposoby. Większość z nich podchodzi do historii w skromniejszy, mniej spektakularny sposób, ale nie porzucając ambicji wiernego odtworzenia czasów, które portretują. Filmy skoncentrowane na relacjach rodzinnych i międzyludzkich, takie jak Różyczka Jana Kidawy-Błońskiego czy Rewers Borysa Lankosza również opowiadają o życiu w czasach komunistycznych, jednak próbują to zrobić bez powtarzania komunałów, podejmując nowe zagadnienia lub wracając do już znanych za pomocą nowych technik. W ostatnich czasach szczególnie dużą rolę odgrywa pamięć jako źródło wiedzy o przeszłości i jako filtr zapośredniczający związane z nią doświadczenia. Przykłady takiego podejścia odnajdziemy w Krecie Rafaela Lewandowskiego, Pokłosiu Władysława Pasikowskiego i Domu złym Wojciecha Smarzowskiego. Dowody archiwalne, wspomnienia krewnych i sam sposób operowania kamerą wykorzystywane są w tych filmach do stawiania pytań o podmiotowość nieodłączną od filmu jako środka poznania przeszłości.
Do przodu w przeszłość: historyczne konteksty w najnowszym filmie polskim
Thomas Anessi, Wydział Anglistyki UAM, Do przodu w przeszłość: historyczne konteksty w najnowszym filmie polskim, Moving Ahead into the Past: Historical Contexts in Recent Polish Cinema, „Images” 2012, vol. XI: (Re)imagining the Past, red. A. Mrozewicz i J. Czaja, nr 20 , s. 5-22, ISSN 1731-450x, język: angielski
Keywords: New Polish Cinema; history in polish film; memory; Dark House; Rewers; Little Rose; The Mole; Consequences; nowe kino polskie; historia w polskim filmie; pamięć; Dom zły; Rewers; Różyczka; Kret; Pokłosie